2015
DOI: 10.7554/elife.11945
|View full text |Cite
|
Sign up to set email alerts
|

Capturing the temporal evolution of choice across prefrontal cortex

Abstract: Activity in prefrontal cortex (PFC) has been richly described using economic models of choice. Yet such descriptions fail to capture the dynamics of decision formation. Describing dynamic neural processes has proven challenging due to the problem of indexing the internal state of PFC and its trial-by-trial variation. Using primate neurophysiology and human magnetoencephalography, we here recover a single-trial index of PFC internal states from multiple simultaneously recorded PFC subregions. This index can exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
89
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(105 citation statements)
references
References 70 publications
16
89
0
Order By: Relevance
“…1b). This signature was subsequently also found in a macaque study of local field potentials (LFPs) from several subregions of the macaque PFC, including the orbitofrontal cortex (OFC), the dorsolateral prefrontal cortex (DLPFC) and the anterior cingulate cortex (ACC), confirming the generality of the mutual inhibition principle across species32.…”
Section: Properties Of the Frameworksupporting
confidence: 52%
See 1 more Smart Citation
“…1b). This signature was subsequently also found in a macaque study of local field potentials (LFPs) from several subregions of the macaque PFC, including the orbitofrontal cortex (OFC), the dorsolateral prefrontal cortex (DLPFC) and the anterior cingulate cortex (ACC), confirming the generality of the mutual inhibition principle across species32.…”
Section: Properties Of the Frameworksupporting
confidence: 52%
“…1d), the DLPFC32 and the lateral intraparietal cortex (LIP)39,42. Data from studies in the dorsal premotor cortex (PMd) are also consistent with a mutual inhibition process.…”
Section: Properties Of the Frameworkmentioning
confidence: 75%
“…Here we found that both decreased levels of GABA and increased levels of glutamate were related to the degree to which a learned task model, as opposed to information displayed on each trial, influenced behavior. This suggests a fundamental difference in function, that dACC represents and regulates the use of a model of the world based on past experiences, rather than that it mediates the integration and selection of all arbitrary types of information during decisions (Hunt et al, 2015). It is particularly in complex environments that monitoring and fine-tuning of how much to use learnt information – as opposed to immediately perceived information - may be crucial.…”
Section: Discussionmentioning
confidence: 99%
“…One simple solution to the Selectivity Problem would be to use a labeled line-each neuron could be designated for a particular option (Padoa-Schioppa, 2011;Hunt et al, 2015). Then comparing values would involve a mutual inhibition between discrete sets of neurons, each set representing the values of its corresponding option.…”
Section: The Selectivity Problemmentioning
confidence: 99%
“…Across many studies, it appears that neurons in several reward-sensitive regions compute and signal, through modulations in their firing rates, the values of available options in an evaluation stage. These value signals are then fed into a comparison stage (which may involve the same neurons and may occur simultaneously) that implements competition through mutual inhibition; this competition probably occurs in multiple areas simultaneously (Strait et al, 2016;Hunt et al, 2015).…”
mentioning
confidence: 99%